Independent relevance of different measures of adiposity for carotid intima‐media thickness in 40 000 adults in UK Biobank - Pillay, P; Carter, JL; Taylor, H; Lewington, S; Clarke, R (Wiley, 2023)
Background Uncertainty persists about carotid intima–media thickness (CIMT) as a marker of subclinical atherosclerosis and the independent relevance of different measures of adiposity for CIMT. We assessed the independent relevance of general adiposity (body mass index), central adiposity (waist circumference), and body composition (fat mass index and fat‐free mass index) with CIMT among adults in the United Kingdom.